ANALISIS HUKUM TERHADAP PENJATUHAN HUKUMAN KEPADA PELAKU TINDAK PIDANA PENGANIAYAAN BERAT (Studi Putusan Nomor 44/PID.B/2018/PN.GST - Angelama Lase (Jurnal Panah Hukum, 2022)
Judges in imposing sentences to perpetrators of criminal acts must be based on applicable law and provide a sense of justice. But sometimes, it is the judge who causes injustice. One of them is the sentence imposed in decision number 44/Pid.B/2018/PN Gst). In the decision, the judge imposed a sentence on the perpetrator of the criminal act of persecution in excess of the maximum penalty as formulated in Article 351 paragraph (2) of the Criminal Code. The type of research used in this research is normative legal research with a statutory approach, case approach, and analytical approach by collecting secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. The data analysis used is descriptive qualitative data analysis. Based on the results of the research and discussion, it can be concluded that the judge's considerations on sentencing the perpetrators of the crime of serious mistreatment (study of decision number 44/Pid.B/2018/PN Gst) are juridical considerations and non-juridical considerations. Juridical considerations are judges' considerations based on the indictment of the public prosecutor and the facts revealed in the trial. Meanwhile, non-juridical considerations are judges' beliefs as regulated in Article 183 of the Criminal Procedure Code. Juridically, the defendant is legally proven to have committed a criminal act of persecution as regulated in Article 351 paragraph (2) of the Criminal Code which stipulates that if the act of torture causes the person to die, he is sentenced to a maximum imprisonment of five years. However, the facts in the decision number 44/Pid.B/2018/PN Gst the judge sentenced him to a sentence of 6 (six) years